2013
DOI: 10.3389/fnins.2013.00180
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and the neurodevelopmental basis of mental illness

Abstract: Epidemiological studies suggest that prenatal exposure to different types of viral or bacterial infections may be associated with similar outcomes; i.e., an increased risk of mental illness disorders in the offspring. Infections arising from various causes have similar debilitating effects in later life, suggesting that the exact pathogen may not be the critical factor in determining the neurological and cognitive outcome in the offspring. Instead, it is thought that response of the innate immune system, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 135 publications
(173 reference statements)
1
81
0
2
Order By: Relevance
“…Moreover, we also evaluated the activity of glucocorticoids as key molecules in the process of stress that may act during this period. Although glucocorticoids are essential for normal brain development, exposure of the fetal brain to an excess of glucocorticoids can also modify fetal brain development and permanently alter the function of the hypothalamic pituitary adrenal axis (HPA) in postnatal life [23][24][25]. There is evidence suggesting that events during prenatal life have longlasting effects during postnatal development and in the adult, for example altering the regulation of the HPA, increasing blood pressure and/or impairing glucose tolerance in the brain [26].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, we also evaluated the activity of glucocorticoids as key molecules in the process of stress that may act during this period. Although glucocorticoids are essential for normal brain development, exposure of the fetal brain to an excess of glucocorticoids can also modify fetal brain development and permanently alter the function of the hypothalamic pituitary adrenal axis (HPA) in postnatal life [23][24][25]. There is evidence suggesting that events during prenatal life have longlasting effects during postnatal development and in the adult, for example altering the regulation of the HPA, increasing blood pressure and/or impairing glucose tolerance in the brain [26].…”
Section: Introductionmentioning
confidence: 98%
“…If this is indeed the case, it could be argued that the observation of release of inflammatory mediators in acute and sub-acute inhalation studies in the first tier would trigger repeated dose toxicity studies that investigate the effects of nanomaterial exposure on reproductive organs and the developing fetus. This is all the more relevant, as both reproductive function and fetal development is indeed sensitive to oxidative stress and inflammation [8,12,13,82,83].…”
Section: Testing Strategymentioning
confidence: 97%
“…If this developmental programming does not match the conditions in postnatal life, physiological dysregulation may arise and affect health later in life [80]. Taking into account that low grade chronic inflammation is a leading mechanism of several disorders in adult humans [81], it might not be surprising that maternal inflammation (along with oxidative stress) may interfere with fetal development and alter organ function in the offspring later in life [8,12,13,[82][83][84]. This could be viewed as an aspect of fetal adaptation to the inflammatory environment of the mother.…”
Section: Indirect Effects Due To Maternal Inflammatory Responsementioning
confidence: 98%
See 1 more Smart Citation
“…Many studies have demonstrated high levels of cytokines and other signs of immune system activation. Furthermore, cytokines are critically involved in early neurodevelopment and deviations from the norm can result in abnormal neuroanatomy and brain chemistry (Howard, 2013; Ratnayake et al, 2013). …”
Section: The Juvenile Onset Of Schizophreniamentioning
confidence: 99%